Anthropocentrism and Environmental Apocalypse in Svetlana Alexievich’s Narrative - Adhikari, Rebati (SCHOLARS: Journal of Arts & Humanities, 2023)
Svetlana Alexievich’s Voices from Chernobyl: An Oral History of Nuclear Disaster (1997) presents how the age of anthropocene is driving the earth towards an imminent peril. In this era, humans acknowledge they are capable of the technological fix, repair and enhancement of natural systems. For instance, the Chernobyl explosion which occurred in 1986 is a consequence of human centered and technocratic worldview. Its aftermath such as a series of apocalyptic events have appeared in the narrative one after the other, and each existence of this biotic community is deadly threatened. Hence, this paper argues that this oral narrative of Alexievich admonishes the humans of this present era to prevent the future catastrophes by unmasking the perilous consequences of the Chernobyl explosion based on the voices of its survivors. To address the issues raised in the paper, the relevant insights of Lawrence Buell, Lynn White, Val Plumwood and Vandana Shiva are taken as a theoretical framework to analyze how and why humans are wrecking nature, and summoning the end times. Finally, this paper concludes that human beings must learn lessons from past deeds and respect nature as a whole entity in order to save the planet.